(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The education of the HR practitioners needs a cutting edge knowledge which may be in advance developments in the law. The example is the Online Social Networks (OSN) in showing work aspirants present workforce. Many of the organization find out off duty behaviour of employees in this trend and they are not violating existing laws. There are still lawful confrontations on the prospect depends on employees’ realistic prospects of confidentiality, showing towards the need of the genuine trade basis in support of not selecting applicants based on the information that is not available from the application and interview process.